The daily exchange rates in Nigeria: 1974 - 2000 Naira/US Dollae and Naira/Pound Sterling - a book of reference. - Olukole, R.A (Lagos R. A. Olukole, 2002)
The book is a reference material on historical, recent and relative exchange rate of the naira to the US dollar and the pound sterling being the two most popular convertible currencies in Nigeria at the time the book was written. It provides an insight into the foreign exchange market makers. The book is most useful for individuals, corporate bodies, institutions and the professionals
Includes bibliographical references.
opc 29/09/16
Ref.
Keywords: Foreign Exchanage Rates; Foreign Exchange Administration; Nigeria